Modulation of Apoptotic Cell Death and Neuroprotective Effects of Glutathione-L-Dopa Codrug Against H2O2-Induced Cellular Toxicity - Sara Franceschelli; Paola Lanuti; Alessio Ferrone; Daniela Maria Pia Gatta; Lorenza Speranza; Mirko Pesce; Alfredo Grilli; Ivana Cacciatore; Emanuela Ricciotti; Antonio Di Stefano; Sebastiano Miscia; Mario Felaco; et al. (MDPI AG, 2019)
The L-3,4-dihydroxyphenylalanine (LD) is the gold standard drug currently used to manage Parkinson’s disease (PD) and to control its symptoms. However, LD could cause disease neurotoxicity due to the generation of pro-oxidant intermediates deriving from its autoxidation. In order to overcome this limitation, we have conjugated LD to the natural antioxidant glutathione (GSH) to form a codrug (GSH-LD). Here we investigated the effect of GSH-LD on H2O2-induced cellular toxicity in undifferentiated and differentiated lymphoma U-937 and dopaminergic neuroblastoma SH-SY5Y cell lines, used respectively as models to study the involvement of macrophages/microglia and dopaminergic neurons in PD. We analyzed the effect of GSH-LD on apoptosis and cellular oxidative stress, both considered strategic targets for the prevention and treatment of neurodegenerative diseases. Compared to LD and GSH, GSH-LD had a stronger effect in preventing hydrogen peroxide (H2O2) induced apoptosis in both cell lines. Moreover, GSH-LD was able to preserve cell viability, cellular redox status, gluthation metabolism and prevent reactive oxygen species (ROS) formation, in a phosphinositide 3-kinase (PI3K)/kinase B (Akt)-dependent manner, in a neurotoxicity cellular model. Our findings indicate that the GSH-LD codrug offers advantages deriving from the additive effect of LD and GSH and it could represent a promising candidate for PD treatment.